Transformational leadership and radical innovation for sustainability: mediating role of knowledge management capability and moderating role of competitive intensity (INMR - Innovation & Management Review, 2023)
Purpose- Drawing on the transformational leadership (TL) and the knowledge-based view, the present study investigates the impact of transformational leadership on radical innovation (RI) through the mediation of knowledge management capabilities (KMC) and moderation of competitive intensity (CI).Methodology- The study's authors collected data from the relevant stakeholders of the industry-university collaboration teams with a structured survey questionnaire. The authors also used a sample of 304 respondents from the textile and apparel industry to test the hypotheses using PLS.Findings- We found that TL positively impacts knowledge management capability and radical innovation. Knowledge management capability positively mediated the relationship between transformational leadership and radical innovation, and this mediation is conditional on the moderating role of competitive intensity for the KMC path to radical innovation. Practical Implications- The study presents a valuable and pivotal insight and an innovative approach for managers and directors of firms in developing countries and emerging countries. The insight, as mentioned earlier, and the innovative approach will help managers and directors to enhance their radical innovation through transformational leadership approaches and knowledge management capabilities resources.Originality- The paper has extended the theory of transformational leadership and KBV by discussing and highlighting the critical role of transformational leadership and KMC in fostering radical innovation.